2011
DOI: 10.1124/jpet.111.189365
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Off-Target Adrenergic Binding and Effects on Cardiovascular Function in the Discovery of Novel Ribosomal S6 Kinase 2 Inhibitors

Abstract: We previously reported the discovery of a novel ribosomal S6 kinase 2 (RSK2) inhibitor, (R)-5-Methyl-1-oxo-2,3,4,5-tetrahydro-1H- [1,4], with high potency (IC 50 ϭ 1.1 nM) targeted for the treatment of heart failure. In the present study, we report that despite nanomolar potency at the target, BIX 02565 elicits off-target binding at multiple adrenergic receptor subtypes that are important in the control of vascular tone and cardiac function. To elucidate in vivo the functional consequence of receptor binding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…To validate RSK as a hit, we performed a dose-response curve using the inhibitors identified by our screen, BIX-RSK2 (referred to as compound 15 in the study by Fryer et al., 2012 ) ( Figure 3 A) and BI-D1870 ( Figure 3 B). These inhibitors have previously been shown to be selective ( Fryer et al., 2012 , Sapkota et al., 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate RSK as a hit, we performed a dose-response curve using the inhibitors identified by our screen, BIX-RSK2 (referred to as compound 15 in the study by Fryer et al., 2012 ) ( Figure 3 A) and BI-D1870 ( Figure 3 B). These inhibitors have previously been shown to be selective ( Fryer et al., 2012 , Sapkota et al., 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…To validate RSK as a hit, we performed a dose-response curve using the inhibitors identified by our screen, BIX-RSK2 (referred to as compound 15 in the study by Fryer et al., 2012 ) ( Figure 3 A) and BI-D1870 ( Figure 3 B). These inhibitors have previously been shown to be selective ( Fryer et al., 2012 , Sapkota et al., 2007 ). It is important to note that BI-D1870 at high concentrations (10 μM or above) can have off-target effects, although this inhibitor was shown to be selective when used at 2.5 μM and lower ( Roffe et al., 2015 , Sapkota et al., 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…The off-target profile of each GPBAR1 agonist was assessed across prototypical BA nuclear receptors as well as 29 additional receptors, ion channels, and other proteins in a selectivity screen at a standard concentration of 10 mM (Eurofins Panlabs, Taipei, Taiwan) and as previously described (Fryer et al, 2012b). The methods for the radioligand binding studies, specific to each assay performed can be found at http://www.…”
Section: Methodsmentioning
confidence: 99%
“…The first was an anesthetized rat hemodynamic model with demonstrated utility and predictivity to detect cardiovascular liabilities for the purpose of both structure-activity relationship-based research (Kym et al, 2006;Fryer et al, 2012b) as well as translation to dogs and humans (Fryer et al, 2012a). Second, a comprehensively instrumented acute model in dogs demonstrated to be predictive of effects in humans using positive controls across a wide range of mechanisms such as inhibitors of cholesterylester transfer protein (CETP), and phosphodiesterase 3 (PDE3), L-type Ca…”
Section: Introductionmentioning
confidence: 99%
“…However, the currently available NTKD inhibitors are not RSK specific (21, 2326) or demonstrate poor pharmacokinetics (27, 28). Covalent inhibitors of the RSK CTKD (2931), targeting autoactivation, are also available and have limited off-target effects.…”
Section: Introductionmentioning
confidence: 99%